Developing an Interactive Digital Flipbook to Enhance Junior High School Students’ Creative Thinking Skills - Arisanti, Titis Dyah; Tinus, Agus; Restian, Arina (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2026)
This study aims to develop and evaluate an interactive digital flipbook as a digital learning medium in science education to foster the creative thinking abilities of junior high school students, particularly in learning about physical and chemical changes and mixture separation. This research utilized a Research and Development (R&D) approach guided by the Four-D model, encompassing the phases of definition, design, development, and dissemination. The research population comprised all seventh-grade students of SMP Muhammadiyah 3 Baron, Nganjuk Regency, in the 2024/2025 academic year. The sample consisted of 13 seventh-grade students selected using a saturated sampling technique. Data were collected through material and media expert validation, pre-test and post-test of creative thinking skills, student response questionnaires, classroom observations, and teacher interviews. The data sources included primary data and secondary data in the form of curriculum documents and relevant literature. Data analysis was conducted using descriptive quantitative and qualitative techniques through percentage analysis and N-Gain calculation. The results indicated that the developed digital flipbook demonstrated a very high level of validity, with scores of 93% from material experts and 99% from media experts. The practicality test showed that the teaching material was very practical, as reflected by a student response score of 84%. The effectiveness test revealed an improvement in students’ creative thinking skills, with the mean score increasing from 61.11 to 74.79 and an N-Gain value of 0.35 (moderate category). Therefore, the interactive digital flipbook is feasible and effective for supporting science learning focused on strengthening creative thinking skills.